Integrated database system for mobile dietary assessment and analysis - Bosch, M.; Schap, T.; Zhu, F.; Khanna, N.; Boushey, Carol; Delp, E. (2011)
Of the 10 leading causes of death in the US, 6 are related to diet. Unfortunately, methods for real-time assessment and proactive health management of diet do not currently exist. There are only minimally successful tools for historical anal- ysis of diet and food consumption available. In this paper, we present an integrated database system that provides a unique perspective on how dietary assessment can be accomplished. We have designed three interconnected databases: an image database that contains data generated by food images, an ex- periments database that contains data related to nutritional studies and results from the image analysis, and finally an enhanced version of a nutritional database by including both nutritional and visual descriptions of each food. We believe that these databases provide tools to the healthcare commu- nity and can be used for data mining to extract diet patterns of individuals and/or entire social groups.